Exploring interactions of plant microbiomes (Scientia Agricola, 2014)
A plethora of microbial cells is present in every gram of soil, and microbes are found extensively in plant and animal tissues. The mechanisms governed by microorganisms in the regulation of physiological processes of their hosts have been extensively studied in the light of recent findings on microbiomes. In plants, the components of these microbiomes may form distinct communities, such as those inhabiting the plant rhizosphere, the endosphere and the phyllosphere. In each of these niches, the "microbial tissue" is established by, and responds to, specific selective pressures. Although there is no clear picture of the overall role of the plant microbiome, there is substantial evidence that these communities are involved in disease control, enhance nutrient acquisition, and affect stress tolerance. In this review, we first summarize features of microbial communities that compose the plant microbiome and further present a series of studies describing the underpinning factors that shape the phylogenetic and functional plant-associated communities. We advocate the idea that understanding the mechanisms by which plants select and interact with their microbiomes may have a direct effect on plant development and health, and further lead to the establishment of novel microbiome-driven strategies, that can cope with the development of a more sustainable agriculture.